Accelerating economic development through women entrepreneurship in SMEs: Bangladesh perspective - Hasanujzaman, Muhammad; Ahmad, Mokbul Morshed; Routray, Jayant Kumar; Pongquan, Soparth; Bangladesh Bank (Pathumthani : Asian Institute of Technology, 2013)
Bangladesh is a country of great potentials. It has a female population of about 50% of total. But in case of participation in labor force and formal economic activities, the number is very insignificant (57%) compared to its male counterpart (84%). Depriving of equal access to education, capital and decision making power of social, political and business sector by women was prevalent that forced them not to come in the mainstream economic activities. But situation has changed significantly in recent years. This is mainly because SME women entrepreneurs show their expertise of dominating in business even with men though confronting a lot of family and social obstacles. Inspired by it, Government of Bangladesh as well as other organizations i.e. Bangladesh Bank, SME Foundation, Ministry of Industries, BWCCI, Commercial Banks have been taking a number of initiatives to bring the women entrepreneurs in the mainstream economic arena to ensure the overall development of the country. For example, Bangladesh Bank made a circular to all commercial banks of Bangladesh pursuing to limit the interest rate for women entrepreneurs by bank rate (which is at currently 5%) plus not more than 5%; i.e. maximum 10% per annum. Besides, GOB has been pursuing a policy for women entrepreneurs in its five-year plan to ensure the equality issues even in economic sector. But, the reality is still grey in terms of implementation of those policies. For instance, the number of women entrepreneurs who got loan from any one of financial institutions in Bangladesh is 27,586 as on June 2013 compared to 17,362 in the previous year. This indicates if provided with training, required capital, infrastructure, and support (family and society) to do business; women entrepreneurs will be able to help accelerate the overall development of the country.
A project submitted in partial fulfillment of the requirements for the degree of Professional Master in Banking and Finance, School of Management
Keywords: Small business -- Bangladesh; Entrepreneurship -- Bangladesh; Women in economic development -- Bangladesh